A Novel Verifiable and Dynamic Fuzzy Keyword Search Scheme over Encrypted Data in Cloud Computing - Xiaoyu Zhu; Qin Liu; Guojun Wang (2016 IEEE Trustcom/BigDataSE/ISPA, 2016)
In recent years, cloud computing becomes more and more popular. Users outsource large amount of encrypted documents to the cloud in order to avoid information leakage. Searchable encryption technique is a desirable service to enable users search on encrypted data. In most existing searchable encryption schemes, they only provide exact keyword search. Fuzzy keyword search improves the system usability because it allows users to make spelling errors or format inconsistencies. Besides, verifiable encryption schemes usually consider a semitrusted server and verify the authenticity of the search results. However, the server may be malicious, which may modify/delete some encrypted files or forge erroneous results in order to save its storage space or computation ability. In this paper, we investigate the searchable encryption problem in the presence of a malicious server, the verifiable searchability is needed to provide users the ability to detect the potential misbehavior. We propose a verifiable and dynamic fuzzy keyword search (VDFS) scheme to offer secure fuzzy keyword search, update the outsourced document collection and verify the authenticity of the search result. Our scheme is proved universally composable (UC) security by rigorous security analysis.